Procrastination Revisited from Academic Stress, Conformity, and Perfectionism of Accounting Student at State University of Malang - Wibowo, Meutia; Fauzan, Slamet (Jurnal Pendidikan Akuntansi & Keuangan, 2024)
This purpose of this study is to determine the effect of academic stress, conformity, and perfectionism on the academic procrastination of accounting students at State University of Malang. The research method used is quantitative research with data collection using questionnaires and sampling techniques using the proportioned stratified random sampling method with samples tested is 221 respondents. Using SPSS version 22, the data analysis method included multiple linear regression. The results of this study indicate that there is a positive influence between academic stress, and conformity on academic procrastination, and the perfectionism variable shows no effect on academic procrastination.